2021
DOI: 10.1002/suco.202000477
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study on seismic performance of shear wall with precast concrete hollow molds

Abstract: A new type of connection between shear walls is proposed for the shear wall with precast concrete hollow molds (PCHM). The overlapping reinforcements are inserted into the PCHM before pouring concrete into the hollow in this method. Full‐scale test specimens are tested under low cyclic loading test to analyze their seismic performance, such as failure modes, hysteretic characters, stiffness degradation, energy dissipation, and ductility. For the precast specimen, although the penetrating crack appears at the h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…In summary, the USC of the CCSSW can be obtained according to Equation (15). Since the parameters of two coupled walls are the same in this paper, the resistance bending moment of the coupled wall itself is M 1 = M 2 , as shown in Equation (18). To verify the correctness of the formula, referring to the calculation data of some models calculated in Section 3, the calculation section is the bottom surface of the coupled wall, so in Equations ( 11) and ( 12), u = 0 and V 1 = V 0 .…”
Section: Validation Of the Theoretical Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…In summary, the USC of the CCSSW can be obtained according to Equation (15). Since the parameters of two coupled walls are the same in this paper, the resistance bending moment of the coupled wall itself is M 1 = M 2 , as shown in Equation (18). To verify the correctness of the formula, referring to the calculation data of some models calculated in Section 3, the calculation section is the bottom surface of the coupled wall, so in Equations ( 11) and ( 12), u = 0 and V 1 = V 0 .…”
Section: Validation Of the Theoretical Methodsmentioning
confidence: 95%
“…Zheng et al, 10 Ghodratian-Kashan et al, 11 Qiu et al, 12 Emami et al, 13 and Tong et al, 14,15 studied the hysteretic behavior of corrugated steel plate shear wall. Li et al, 16,17 Zhang et al, 18 and Sun et al 19 studied the mechanical properties of precast concrete shear walls under lateral loads.…”
Section: Introductionmentioning
confidence: 99%
“…Zhang found that when the interface shear strength is greater than the shear stress and the interface tensile strength exceeds the radial tensile stress, a superimposed structure is formed. Otherwise, a composite structure is formed [15]. Therefore, in addition to testing the compressive strength and flexural strength of mortar materials, it is also necessary to study the splitting tensile strength and shear strength of the interface between mortar and concrete.…”
Section: In Situ Spraying Mortar Materials Performance Experimentsmentioning
confidence: 99%
“…Zhang determined that when the coordinated deformation of the existing pipeline lining depends on the relationship between the load on the interface and the interface resistance, and if the resistance is greater than the load, the two form a superimposed composite structure. An indoor test of the composite structure model indicated that the bearing capacity of the upper and lower beams could not be fully exerted due to the gap caused by the shrinkage of the mortar layer, which was approximately 0.6-0.9 times the theoretical value [6]. WRC studied the influence of the modulus of the mortar layer on the bearing capacity of the repaired pipeline.…”
Section: Introductionmentioning
confidence: 99%